Immune Checkpoint Inhibitors in the Treatment of Patients With Cancer and Preexisting Psoriasis: A Systematic Review and Meta-Analysis of Observational Studies - Yu, Yixuan; Zhou, Yang; Zhang, Xu; Tan, Kexin; Zheng, Jiabin; Li, Jia; Cui, Huijuan (Frontiers in Oncology, 2022)
Background: Immunotherapies represented by immune checkpoint inhibitors (ICIs) have revolutionized cancer treatment. A large population has both cancer and psoriasis, but are usually excluded from ICI clinical trials because of the dysregulated activation of the immune system. This is the first study to evaluate the safety and efficacy of ICI therapy in patients with cancer and pre-existing psoriasis. Methods: PubMed, EMBASE, Cochrane, and MEDLINE databases were searched from inception through February 2022. Observational studies on patients with cancer and confirmed psoriasis before ICI initiation were included. Outcomes included the incidence of psoriasis flares, de novo immune-related adverse events (irAEs), discontinuation rate due to flare/de novo irAEs, and efficacy of ICI therapy. Clinical manifestations, management, and outcomes for adverse events (AEs) were systematically reviewed. All pooled analyses were based on a random-effects model using Stata software. Meta-regression and subgroup analyses were performed to identify sources of heterogeneity. Results: Twelve studies involving 191 patients were included. The pooled incidence of psoriasis flares was 48.2% [95% confidence interval (CI): 41.7-54.7%, I2=71.7%] and 44.9% (95% CI: 29.0-60.7%, I2=71.8%) for de novo irAEs. The tumor type, psoriasis subtype, ICI class, and country were the main sources of heterogeneity. Grades 3-4 flares occurred in 10.8% (95% CI: 10.7-22.5%) of patients and about 16.6% (95% CI: 10.7-22.5%) of patients experienced grades 3-4 de novo irAEs. The estimated incidence of ICI discontinuation due to AE was 18.5% (95% CI: 6.1-30.8%, I2=68.7%). The median times to develop flare and de novo irAEs were 44 and 63 days, respectively. Endocrinopathies and colitis were the most common de novo irAEs. Conventional therapy is effective for most AEs. The estimated objective response rate (ORR) of ICIs was 38.1% (95% CI: 11.8-64.3%, I2=81.7%) and the disease control rate (DCR) was 64.5% (95% CI: 55.3-73.8%, I2=0). Conclusions: The flare of patients with cancer and pre-existing psoriasis treated with ICI therapy is frequent, but the incidence of de novo irAEs and the efficacy of ICI therapy are comparable to that of the general population. Most AEs are mild and manageable with conventional therapy, which required discontinuation of ICI therapy in 18.5%.